Lifecycle Multi-colony Bee Algorithm for solving Flexible Job Scheduling Problems - Liling Sun, Yuhan Wu, Xiaodan Liang, Maowei He, Hanning Chen, (Design Engineering, 2020)
We present a Lifecycle Multi-colony Bee Algorithm (LMcBA) for Flexible Job-shop Scheduling Problem (FJSP). This problem has a strong practical background in process industry. Existing approaches considering constant processing time may not be appropriate to address FJSPs. To make evolutionary algorithm applicable in FJSP, a novel Lifecycle Multi-colony Bee Algorithm is chosen as the core optimization algorithm of the FJSP. Experimental results show LMcBA has an outstanding performance in solving FJSP.